Fibrinolysis-Mediated Pathways in Acute Liver Injury - Capece, Gina E.; Luyendyk, James P.; Poole, Lauren G. (Seminars in Thrombosis and Hemostasis, 2024)
Acute liver injury (ALI), that is, the development of reduced liver function in patients without preexisting liver disease, can result from a wide range of causes, such as viral or bacterial infection, autoimmune disease, or adverse reaction to prescription and over-the-counter medications. ALI patients present with a complex coagulopathy, characterized by both hypercoagulable and hypocoagulable features. Similarly, ALI patients display a profound dysregulation of the fibrinolytic system with the vast majority of patients presenting with a hypofibrinolytic phenotype. Decades of research in experimental acute liver injury in mice suggest that fibrinolytic proteins, including plasmin(ogen), plasminogen activators, fibrinolysis inhibitors, and fibrin(ogen), can contribute to initial hepatotoxicity and/or stimulate liver repair. This review summarizes major experimental findings regarding the role of fibrinolytic factors in ALI from the last approximately 30 years and identifies unanswered questions, as well as highlighting areas for future research.
Keywords: acetaminophen; plasminogen; tissue plasminogen activator; fibrinogen